Economic repercussions of marital infidelity. Issue 1 (14th March 2016) - Crouch, Elizabeth; Dickes, Lori
Abstract : Purpose: – Numerous scholars have studied the propensity and related determinants of marital infidelity across socioeconomic and demographic groups. However, the broader social and economic consequences of infidelity remain an unexplored question, particularly the macroeconomic consequences from the individual impacts on families and households. The paper aims to discuss these issues. Design/methodology/approach: – Using income data from the Bureau of Labor and Statistics, the purpose of this paper is twofold: first, to analyze the relationship between the probability of infidelity and income and second, to quantify the cost of marital infidelity on individual families and taxpayers. The results confirm that infidelity makes individual households poorer, but goes further to reveal widespread negative externalities that fall to taxpayers from the consequences of family fragmentation. Findings: – The results of this study indicate a review of government policy since numerous government policies contradict the incentive to stay married. Future research should consider additional estimations of the full range of costs related to infidelity and family fragmentation with particular focus on the public programs that may absorb the brunt of the negative externalities resulting from divorce. Research limitations/implications: – This research confirms earlier research that infidelity has a high probability of causing divorce. Combined with this research, the analysis confirms a statistically significant negative relationship between infidelity and income and that when infidelity causes divorce, the results are substantial public economic and social costs. By definition public economic and social costs are borne by society, resulting in increased taxpayer burdens for society at large. Practical implications: – Previously, the consequences of infidelity were a largely unexplored question. There had been some work on the probability of infidelity but little beyond this. Further, there had been minimal literature on the social efficiency of infidelity, especially research focussing on the external costs imposed on third parties such as children and taxpayers (Smith, 2012). This work took earlier research further by first confirming the negative impact on household income based on the probability of infidelity. Additionally, this is the only study that has examined the economic consequences of divorce due to infidelity. This research confirms that the presence of infidelity, especially when it leads to divorce, results in substantial economic and social externalities resulting from family fragmentation. Future research would benefit from a more in depth understanding of the characteristics that relate to the increased probability of infidelity, separate from and in conjunction with divorce. Furthermore, examining costs as they relate to specific programs, like Temporary Assistance for Needy Families, may clarify the impact of family fragmentation on specific programs. Additionally, the results from this study can be incorporated into larger sets of findings focussing on government policy to better understand the full range of social implications from infidelity. Social implications: – Future research should consider additional estimations of the full range of costs related to infidelity and family fragmentation, with particular focus on the public programs that may absorb the brunt of the negative externalities resulting from divorce. The most pertinent policies influencing the rate of marriage and divorce in the USA are the income tax code, Social Security spousal and survivor benefits, the Earned Income Tax Credit, child support enforcement, Temporary Assistance to Needy Families, food stamps, Medical, Supplemental Security Income, and WIC (Burstein, 2007). A review of these policies and their incentive structure related to family cohesiveness should be considered as a part of larger cost/benefit analysis of these programs. Originality/value: – This work took earlier research further by first confirming the negative impact on household income based on the probability of infidelity. Additionally, this is the only study that has examined the economic consequences of divorce due to infidelity. This research confirms that the presence of infidelity, especially when it leads to divorce, results in substantial economic and social externalities resulting from family fragmentation.